Distinction between super-cooled water and ice with high duty cycle time-of-flight neutron imaging - Siegwart, Muriel Dorothea (2019)
We report on measured neutron cross section data for super-cooled water and ice by time-of-flight neutron transmission imaging. In particular we demonstrate the use of high duty cycle time-of-flight (HDC-TOF) measurements to determine the local aggregate state of water with spatial resolution, by exploiting the neutron cross section dependence on the mobility of hydrogen atoms for long neutron wavelengths (> 4 Å). While one can envision many different applications for this method, one example is to provide insights into the freezing mechanism during the start-up of polymer electrolyte fuel cells from below zero degrees. Unlike for other wavelength selective measurements (e.g. Bragg edge imaging), only a limited wavelength resolution is required for this method. With a chopper setup with high duty cycle (30 %), we reached a high contrast-to-noise ratio (CNR) with a contrast between ice and super-cooled water of 8 %. To maximize the CNR, we optimized the duty cycle, pulse period and image processing parameters. Moreover, we present a theoretical framework for performing such optimization calculations, which can be used to maximize CNR for any beam line and any substances. For the optimization procedure presented in this publication, we used cross section values for ice and super-cooled water measured with high wavelength resolution using wavelength frame multiplication choppers. Our results show that the aggregate state of water of a sufficiently thick layer of water (> 0.5 mm) can be reliably determined for a small area (1 mm2 ) and with a reasonable short acquisition time of 5 minutes.